Collaborative Social Work Practices in Multi-Service Female Juvenile Rehabilitation: A Case Study of ATENSI Implementation in Indonesia - Bambang Rustanto; Tuti Kartika; Ayi Haryani; Dwi Yuliani; Susilawati Susilawati; Nisa Almalia Nurfauziah (Westscience Press, 2026)
This study investigates collaborative social work practices in the context of female juvenile rehabilitation in Indonesia, focusing on the operationalization of the ATENSI (Social Rehabilitation Assistance) framework. Triggered by the increasing vulnerability of adolescent girls, the research explores how integrated, multi-stakeholder, and trauma-informed approaches can enhance institutional care. While ATENSI offers a policy-level shift toward inclusive and holistic service delivery, its implementation in gender-specific settings remains underexplored. Using a mixed-methods sequential explanatory design, the study combines survey data from 75 social workers with qualitative insights from interviews, focus group discussions, and field observations at two major rehabilitation centers. Findings reveal strong internal collaboration, particularly between social workers and psychologists, but limited integration of vocational trainers and external stakeholders, such as NGOs and local governments. Barriers include digital inequities, absence of trauma-informed SOPs, role ambiguity, and sociocultural taboos related to female trauma. The study contributes both empirical and conceptual advancements to global social work discourse. Empirically, it maps gender-responsive collaboration dynamics in a rarely studied Global South context. Conceptually, it introduces the ATENSI Gender-Responsive Collaborative Framework—an integrative model synthesizing collaborative governance, networked social work, and trauma-informed gender-sensitive practice. This research addresses a critical knowledge gap by offering a scalable, context-adaptive model for institutional rehabilitation systems dealing with compounded vulnerabilities in adolescent girls. Its findings are relevant for international audiences seeking to strengthen collaborative practices in gender-responsive care, particularly in resource-constrained settings.